Implementasi Akhlak terhadap Keluarga, Tetangga dan Lingkungan - Ira Suryani; Hasan Ma’tsum; Gumilang Wibowo; Ali Sabri; Rika Mahrisa (Islam & Contemporary Issues, 2021)
The position of morals in human life occupies an important place, both as individuals and as part of members of society and the nation, because the ups and downs of a society depend on how moral it is. As Muslims we already have examples and role models in Islamic morality, the Prophet Muhammad, who was sent by Allah to perfect human morals, is an example for the Islamic ummah in their behavior. Rasulullah Saw guided mankind in their behavior through their actions and words which reflected the morals of a Muslim. If humans are able to follow all the actions of the Prophet, be it actions, traits or characters, then it will be certain that all living things will live in a noble world and in the hereafter.